EVALUATION OF SERVICE QUALITY IN NURSING AND PATIENT SATISFACTION: PERCEPTION OF PATIENTS AND STUDENT NURSES (Proceedings of the Global Public Health Conference, 2019)
Evaluation of service quality and patient satisfaction should be an ongoing process for improving the quality of patient care. Quality of caring behaviour significantly impact on patient satisfaction. The aim of this study was to determine the service quality of nursing care through patients’ and student nurses’ perception on nurses’ caring behaviours and patient satisfaction. This descriptive study was conducted in 2018 in the surgical and medical wards of a leading hospital in Southern Province, Sri Lanka. The study population was patients (N=300) and 3rd-year student nurses (N=115). Random sampling technique was used. Validated and modified 5 point-Likert scales of “perception of caring-behaviors” and “SERVQULAL” were employed. Jean Watson’s theory of human caring was incorporated in the study. Descriptive analysis, Pearson’s correlation, and regression analysis were performed. The mean was computed (1-5) and higher score reflected positive perception. Patients’ perception was above average level on caring behaviour (4.07±0.54) and satisfaction (3.21±0.64). There was a strong correlation between perceived caring behaviour and patient satisfaction (Pearson Correlation 0.65). Findings revealed that patients rated higher in terms of caring behavior compared to the ratings of student nurses (3.47±0.65) and there was a significance difference between two groups (0.03< 0.05). According to regression analysis between independent (caring behaviour) and dependent variable (satisfaction), R2 was 0.44. Jean Watson’s theory of care, bedside handover, information provision to the patients, empathetic approach and patients’ awareness on ideal nursing care are recommended to further increase quality and satisfaction. Area of culturally appropriate therapeutic touch is recommended for future research.
Keywords: quality nursing care; patient satisfaction; caring behaviors.